2013
DOI: 10.1128/iai.01346-12
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Protection against Bacillus cereus-Mediated Respiratory Anthrax-Like Disease in Mice

Abstract: cBacillus cereus strains harboring a pXO1-like virulence plasmid cause respiratory anthrax-like disease in humans, particularly in welders. We developed mouse models for intraperitoneal as well as aerosol challenge with spores of B. cereus G9241, harboring pBCXO1 and pBC218 virulence plasmids. Compared to wild-type B. cereus G9241, spores with a deletion of the pBCXO1-carried protective antigen gene (pagA1) were severely attenuated, whereas spores with a deletion of the pBC218-carried protective antigen homolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 54 publications
2
14
0
Order By: Relevance
“…However, despite the fact that B. anthracis and G9241 both produce encapsulated bacilli and anthrax toxin, studies in mice and rabbits demonstrate that G9241 exhibits virulence similar to the attenuated, un-encapsulated B. anthracis Sterne (pXO1 ϩ /pXO2 Ϫ ) strain. Additionally, G9241 genetic knockouts of the two PA homologs demonstrated that pBCXO1-encoded PA is required for virulence in mice (16). This is consistent with the pathogenesis of G9241 being toxin-mediated, whereas the absence of the poly-D-glutamic acid capsule may account for the virulence attenuation when compared with the fully virulent B. anthracis Ames strain (15).…”
supporting
confidence: 67%
“…However, despite the fact that B. anthracis and G9241 both produce encapsulated bacilli and anthrax toxin, studies in mice and rabbits demonstrate that G9241 exhibits virulence similar to the attenuated, un-encapsulated B. anthracis Sterne (pXO1 ϩ /pXO2 Ϫ ) strain. Additionally, G9241 genetic knockouts of the two PA homologs demonstrated that pBCXO1-encoded PA is required for virulence in mice (16). This is consistent with the pathogenesis of G9241 being toxin-mediated, whereas the absence of the poly-D-glutamic acid capsule may account for the virulence attenuation when compared with the fully virulent B. anthracis Ames strain (15).…”
supporting
confidence: 67%
“…Nevertheless, this was the first study to explore the contribution of LF to virulence of the G9241 strain. A ΔpagA1 mutant strain of G9241 was previously assessed for lethality after intraperitoneal challenge of C57BL/6 mice with 10 5 spores; the ΔpagA1 mutant caused fewer deaths at that dose than WT G9241 (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in single intraperitoneal (i.p.) challenge dose studies with C57BL/6 mice, the hyaluronic acid capsule and PA1 were required for full virulence of G9241, while PA2 did not appear to contribute to pathogenicity at an inoculum of 10 5 spores (19,20). In this study, we sought to better characterize the role of toxins in pathogenesis of G9241.…”
mentioning
confidence: 99%
“…The data from this study suggest that even though the TNA serum titers generated by the rLFn and pPAho‐rPA vaccination regimens were ninefold (79 μg mL −1 ) and 171‐fold (4 μg mL −1 ) lower, respectively, than that for the rPA (684 μg mL −1 ) vaccination schedule, they were still sufficient to confer complete protection from challenge and suggest a threshold serum TNA level to achieve robust protection against B. cereus G9241 spore challenge for this study's experimental conditions. Recently, it has been demonstrated that mice immunized with the FDA‐approved AVA vaccine are protected against challenge with B. cereus G9241 spores (Oh et al ., ). Here, we demonstrate for the first time that fully defined DNA‐ and protein‐based anthrax toxin vaccines can also confer protection against lethal aerosol challenge with B. cereus G9241 spores in Dunkin Hartley guinea pigs.…”
Section: Tna Serum Fractions Compared With Total Antigen‐specific Iggmentioning
confidence: 99%
“…The viability of using an anthrax PA-based vaccine as a prophylactic against B. cereus G9241 infection was recently demonstrated (Oh et al, 2013). AVA-immunized C57BL/6 mice exhibited robust protection against exposure to B. cereus G9241 spores via both the intraperitoneal (100% survival at 379 LD 50 ) and aerosol (90% survival at 309 LD 50 ) routes of infection.…”
Section: Introductionmentioning
confidence: 99%